Reduction in broad-spectrum antimicrobial prescriptions by primary care pediatricians following a multifaceted antimicrobial stewardship program - Pagano, F; Amato, C; De Marco, G; Micillo, M; Cecere, G; Poeta, M; Guarino, A; Lo Vecchio, A (Frontiers in Pediatrics, 2023)
Background Since 2016, following the Italian “National Plan to Contrast Antimicrobial Resistance”, Campania Region has implemented an antimicrobial stewardship program, including the obligation to associate an appropriate International Classification of Diseases-9 code to each antibiotic prescription, the publication of schemes for empirical antibiotic therapy and educational interventions. Methods To evaluate the impact of these interventions on the prescribing habits of family pediatricians, we conducted a retrospective cohort study (January 2016 - December 2020), including all patients registered in an associate practice of Primary Care Pediatricians. We collected data on antibiotic prescriptions through a specific study management software; our primary outcomes were the annual prescription rates, calculated for both the number of patients in follow-up and the number of medical consultations, and the annual prescription rates for selected antibiotic classes and molecules. To investigate the hypothesis that chronic conditions would be associated with an increased rate of prescription, we also tested the association between underlying conditions and the number of antibiotics received. Results During the study period, 2599 children received 11364 antibiotic prescriptions (mean 4.37, SD 4.28). From 2016 to 2020 we observed a substantial reduction in both the annual prescription rate per 100 patients (9.33 to 3.39; R2=0.927; p=0.009), and the annual prescription rate per 100 medical consultations (25.49 to 15.98; R2=0.996 p<0.01). The prescription rates of Amoxicillin-Clavulanate (50.25 to 14.21; R2=0.983, p=0.001) and third generation Cephalosporins (28.43 to 5.43; R2=0.995, p<0.01) significantly decreased; we didn’t find significant modifications in the prescription rates of Amoxicillin and Quinolones; finally, we observed a trend toward reduction in the prescription of Macrolides. No statistical association was found between antibiotics prescribing frequency and history of chronic diseases. Discussion Following the implementation of the regional interventions on antimicrobial stewardship, we observed a substantial reduction in the overall antibiotic prescription per patients and per medical consultations, with a statistically significant reduction in the use of broad-spectrum molecules. Considering the results of our analysis, new guidance and training interventions addressed to specialists in the Primary Care sector should be implemented to further limit antibiotic resistance.